Atitudes de profissionais da Rede de Atenção Psicossocial frente ao adoecimento mental - Aline Mara Gonçalves; Sueli de Carvalho Vilela; Fábio de Souza Terra (Universidade Federal do Ceará, 2017)
Objective: to investigate the attitudes of professionals of the Network of Psychosocial Attention to mental illness. Methods: cross-sectional and analytical study. Two instruments were used: the characterization questionnaire and the Opinions Scale about Mental Illness, answered by 80 employees of the Psychosocial Attention Network. For counting the obtained points, pre-established formulas were used; and for correlations and associations, non-parametric tests according to the normality of the data. Results: the attitudinal profile denominated Authoritarianism was characterized by a higher average in the population, followed by the Social Restriction and Etiology of Mental Effort profiles. It was also observed that the variables schooling, working time in mental health services and monthly family income showed significant correlations in relation to the types of attitudes. Conclusion: the attitudinal profile of the studied population reflects predominantly authoritarian, restrictive and discriminatory attitudes.